Pengaruh Total Asset Turnover, Current Ratio, dan Debt To Equity Ratio Terhadap Return On Equity Pada Perusahaan Manufaktur Sub Sektor Tekstil dan Garmen Yang Terdaftar Di BEI 2016-2022 - Rahman, Hada Apriani; Salam, Anis Fuad; Hikmat, Imat (Pascasarjana Universitas Primagraha, 2023)
The textile and garment industry sector is an industry that processes fiber into yarn or fabric. This research is aimed at analyzing and determining the influence of Total Asset Turnover, Current Ratio, and Debt to Equity Ratio on Return On Equity. Testing is carried out both partially and simultaneously with the research methods used are descriptive methods and verification methods. This research used seven samples of companies with a total of 49 data. The results of this research indicate that Total Asset Turnover has a significant effect on Return On Equity. Meanwhile, the Current Ratio and Debt to Equity Ratio variables do not have a significant effect on Return On Equity. Simultaneously, the variables Total Asset Turnover, Current Ratio, and Debt to Equity Ratio do not have a significant effect on Return On Equity.